Into the unknown': a comparative study of figurative language in German, Tamil, and English - Sivan, Pavita; Mohd Jalis, Farhana Muslim (Nexus Publishing, 2024)
Figurative language is vocabulary used creatively, departing from its literal meaning. The song is one of the resources used by language learners to fill in the gaps between one another. This study was done for non-native speakers of foreign languages who might have trouble understanding figurative language. This study aims to find the most common figurative language among the three languages. Perrine's theory is applied in this study to analyze figurative language. Tilly’s theory was applied to analyze the contextual meaning of figurative language. The types of figurative language were analyzed in this study using a qualitative method. There are 37 types of figurative language from the English version, 22 from the Tamil version, and 29 from the German version. The English version is the most frequently used figurative language among the three languages. Therefore, researchers in the future should examine the parallels, differences, and trends in the use of figurative language in these languages, according to this study.